Effect of replacing fish meal with soybean meal on growth, feed utilization and nitrogen and phosphorus excretion of juvenile Pseudobagrus ussuriensis. (17th April 2015) - Wang, Yuyu; Yu, Shiliang; Wang, Yueyang; Che, Jianfang; Zhao, Liping; Bu, Xianyong; Yang, Yuhong
Abstract: An 8‐week feeding trial was conducted to evaluate the effects of replacing fish meal with soybean meal (SBM) on growth, feed utilization, and nitrogen (N) and phosphorus (P) excretion of juvenile Pseudobagrus ussuriensis (initial average weight 0.50 ± 0.00 g). Seven isonitrogenous and isolipidic diets were formulated to contain SBM to replace fish meal protein at 0% (S0), 10% (S10), 20% (S20), 30% (S30), 40% (S40), 50% (S50) and 60% (S60) respectively. To investigate the effects of supplementation with crystalline amino acid to balance diet S60, one diet was formulated to add 0.30% methionine (SM60). The results showed that there was no significant difference in weight gain among fish fed S0, S10, S20, S30 and S40 diets, however, a significant reduction in this variable occurred when 50% and 60% of fish meal protein was replaced by SBM ( P  < 0.05). Apparent digestibility coefficients of dry matter, crude protein and phosphorus of diets were affected by dietary SBM levels. N and P excretion indicate that fish meal replacement by SBM led to an increase in N excretion, but led to a reduction in P excretion. No differences were detected in growth, feed utilization and N and P excretion between fish feed diets S60 and SM60. The results of this study show that 40% of fish meal protein could be replaced by SBM in diets of juvenile P. ussuriensis without having a significant negative effect on growth or feed efficiency, but that higher dietary SBM levels reduce fish performance.